The Effect of Music Therapy on Blood Pressure in Hypertensive Patients Treated at Sobirin Lubuk Linggau Hospital - Neni Triana; Hanifah Hanifah; Novaria Novaria (Jurnal Sains Kesehatan, 2019)
Hypertension is one of desease that can caused death in the world. Hypertension can be stated as a “silent killer” because someone who diagnosed wit hypertension in organ vital that severe. The aims of this study is to determine effect of music therapy on blood pressure in hypertensive patients treated at Sobirin Lubuk L, canggau Hospital.The Quasi Experimental research method uses The One Group Pretest Posttest Design. The population in this study were all hypertensive patients treated in the Nusa Indah room, Sobirin Lubuk Linggau Hospital as many as 38 people. The sampling technique in this study used Total Sampling. Data collection is done using primary data, namely data obtained through direct measurement of blood pressure using sphygmomanometer in hypertensive patients in the Nusa Indah room at Sobirin Lubuk Linggau Hospital. Data analysis was done by univariate, bivariate with Chi-Square Test.The results were obtained: (1) Of the 38 hypertensive patients treated in the Nusa Indah room at Sobirin Lubuk Linggau Hospital before music therapy was given, systolic blood pressure was obtained with a minimum value of 130 mmHg, a maximum value of 160 mmHg, an average value of 142.63 mmHg and diastolic blood pressure with a minimum value of 80 mmHg, a maximum value of 100 mmHg, an average value of 92.37 mmHg; (2) Of the 38 hypertensive patients treated in the Nusa Indah room at Sobirin Hospital Lubuk Linggau after music therapy was given blood pressure was obtained with a minimum value of 120 mmHg, a maximum value of 150 mmHg, an average value of 135.79 mmHg and blood pressure systole with minimum value of 80 mmHg, maximum value of 90 mmHg, average value of 83.42 mmHg; (3) There is the influence of music therapy on the reduction of blood pressure in hypertensive patients who are treated at Sobirin Lubuk Linggau Hospital. The results of this study can be input for the SobirinLubukLinggau Hospital to be able to apply non-pharmacological therapies such as music therapy to help reduce blood pressure other than drugs. Keywords: blood pressure, music therapy, patient